Personal exposure of Paris office workers to nitrogen dioxide and fine particles. Issue 8 (1st August 2002) - Mosqueron, L; Momas, I; Le Moullec, Y
Abstract : Aims: (1) To obtain an overall estimate of variability of personal exposure of Paris office workers to fine particles (PM2.5 ) and nitrogen dioxide (NO2 ), and to quantify their microenvironmental determinants. (2) To examine the role of potential determinants of indoor concentrations. Methods: Sixty two office workers in a Paris municipal administration (all non-smokers) were equipped with personal samplers: passive samplers for 48 hours for NO2 (n = 62), and active pumps for 24 hours for PM2.5 (n = 55). Simultaneous measurements were performed in homes and offices; the local air monitoring network provided ambient concentrations. A time activity diary was used to weight measured concentrations by time spent in each microenvironment in order to estimate exposure concentrations. Results: On average, PM2.5 personal exposure (30.4 μg/m 3 ) was higher than corresponding in-home (24.7 μg/m 3 ) and ambient concentrations (16.7 μg/m 3 ). Personal exposure to NO2 (43.6 μg/m 3 ) was significantly higher than in-home concentrations (35.1 μg/m 3 ) but lower than the background outdoor level (60.1 μg/m 3 ). Personal exposures to PM2.5 and NO2 were not significantly different from in-office concentrations. PM2.5 and NO2 personal exposures were not significantly correlated. In-home, in-office, in-transit, outdoor time weighted concentrations, and time spent in other indoor microenvironments explain respectively 86% and 78% of personal variations in PM2.5 and NO2 . In-home PM2.5 concentration was primarily influenced by exposure to environmental tobacco smoke, and secondly by the ambient level (R 2 = 0.20). NO2 in-home concentration was affected mostly by the ambient level and gas cooking time (R 2 = 0.14). Conclusion: While results show the major contribution of in-home and in-office concentrations to both NO2 and PM2.5 personal exposures, the identification of indoor level determinants was not very conclusive.